Genome Sequence of Naphthalene-Degrading Soil Bacterium Pseudomonas putida CSV86 - Phale, Prashant S. (American Society for Microbiology, 2013)
Pseudomonas putida CSV86, a soil isolate, preferentially utilizes naphthalene over glucose as a source of carbon and energy. We present the draft genome sequence, which is 6.4 Mb in size; analysis suggests the chromosomal localization of genes coding for naphthalene utilization. The operons coding for glucose and other aromatic compounds might also be annotated in another study.